A toponymic network in the southern Andean region: What is behind it? - Cortez Torres, Eunice (2007)
The toponym Chuqik'iraw is a name formed by two lexemes, one of Aymara origin and the other of Quechua origin. When analyzing the meaning of the lexeme chuqi, we can see that it carries a great significance, since it is the name with which the inhabitants of Ancient Peru called the metal par excellence: gold. On the other hand, it is striking that this lexeme is recurrent in its appearance for so many other toponyms in the same Andean area: the highlands of southern Peru. It is from this phenomenon that we consider that there is a network of toponyms that are linked in their meaning and Andean cosmogony through the lexeme chuqi. Chuqik'iraw would be one of these spaces that we could call sacred, because they manifest the feelings and beliefs of a people for whom the symbol is part of their daily life.